The Psychology and Historical Perspective behind Entrepreneurial and Business Practices in Indonesia - Muhammad Asif Khan (International Journal of Digital Entrepreneurship and Business, 2020)
Indonesia is a country in southern Asia consisting of many islands and is the 4th largest populated country in the world. The country has one of the best economies in the world since it has been participating in international trade for many years. However, it has had drawbacks that have made it unable to reach the levels of the developed countries in the world. Therefore, it is necessary to study the facts behind the success and the failure of some business ventures. Additionally, the study of strategies by companies to have a competitive advantage in business is fundamental to understanding the situation in the country. The new research will seek to use the available analyses about the same topic to bring about a new understanding. Theories such as McClelland’s locus of control theory can apply in the study to understand the relationship between entrepreneurship and the psychology of people. The paper uses secondary sources review to get information about the topic to propose a solution to the challenges that the companies in the country have been facing towards achieving a competitive returns.